2021
DOI: 10.1111/acem.14428
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of instruments to measure health literacy of patients in emergency departments

Abstract: Health literacy (HL) is the individuals' capacity to obtain, process, and understand basic health information and services needed to make appropriate health decisions. 1 Important HL skills include reading and writing ability and numeracy skills. HL is an important determinant for health behavior, including planning and adjusting lifestyle, participation in medical decision making, treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…These constructs do not fully represent the range of skills required by a parent who must provide care to a child with cancer, which involves properly adhering to medication schedules, understanding infection risks, administering medications correctly, and recognizing when to seek emergent medical care (Haugen et al, 2016). In a systematic review, Hesselink et al (2022) reported inconsistent validity of the BHLS when tested against other more comprehensive measures of health literacy. Additionally, when using the NAAL, a more in-depth 28-item assessment of health literacy, investigators found that 46% and 48% of parents, respectively, failed to correctly perform at least one of two medicationrelated or immunization-related tasks (Yin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These constructs do not fully represent the range of skills required by a parent who must provide care to a child with cancer, which involves properly adhering to medication schedules, understanding infection risks, administering medications correctly, and recognizing when to seek emergent medical care (Haugen et al, 2016). In a systematic review, Hesselink et al (2022) reported inconsistent validity of the BHLS when tested against other more comprehensive measures of health literacy. Additionally, when using the NAAL, a more in-depth 28-item assessment of health literacy, investigators found that 46% and 48% of parents, respectively, failed to correctly perform at least one of two medicationrelated or immunization-related tasks (Yin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Using data from these studies, Landier et al (2016) convened an expert panel to evaluate the evidence and develop recommendations, establishing the importance of limiting parent education at the time of diagnosis to include only essential elements, with the goal of reducing information overload. Recently, Hockenberry et al (2021) provided evidence that a standardized new diagnosis pediatric oncology discharge education plan can be successfully implemented across multiple institutions. Hockenberry et al (2021) also established that discharge plans focused on symptom management, compared with those focused on coping with a new cancer diagnosis, were most helpful to parents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them also involve more cognitive effort and could stigmatize or embarrass patients with low health literacy [23]. Accordingly [24], self-reported health literacy instruments, which are easy to apply in a clinical setting, have become increasingly popular in recent decades. Rapid and accurate screening tools for identifying patients with low health literacy could help guide interventions and improve care in primary care settings.…”
Section: Of 11mentioning
confidence: 99%
“…Among other obstacles, the implementation of geriatric screening is often limited by the perception that it is not a priority or is too time consuming, 6 in addition to a cultural resistance to providing these services which are seen as outside of the ED's core mission to provide timely acute care 8,9 . Moreover, EDs are already required by government mandate and other national guidelines to screen patients for a variety of conditions including alcohol abuse, 10 domestic violence, 11 suicide risk, 12 and low literacy 13 . There are many more competing demands for screening than there are minutes to ask additional questions during an ED encounter, and little enthusiasm from providers for adding additional screening to the ED workflow 8,14,15 …”
Section: Introductionmentioning
confidence: 99%